2022
DOI: 10.7774/cevr.2022.11.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia areata after COVID-19 vaccination

Abstract: The coronavirus disease 2019 (COVID-19) vaccines are authorized for use in numerous countries worldwide. Several cutaneous findings are reported after severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) vaccination. Here, we report the case of a patient with a rapid onset of alopecia areata immediately after receiving the second dose of the COVID-19 vaccine. Alopecia areata is a common autoimmune disease leading to non-scarring hair loss. Among the many cutaneous adverse effects reported after the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…Many case reports and studies of hair involvement reported after COVID‐19 vaccination have been published in the literature. 35 , 36 , 37 Nonetheless, since our study focused on cutaneous reactions, hair involvement after COVID‐19 vaccination was not examined separately. However, the current study also had several strengths, such as more than 95% of non‐local cutaneous reactions being diagnosed by a dermatologist and the participants being questioned through one‐to‐one interviews.…”
Section: Discussionmentioning
confidence: 99%
“…Many case reports and studies of hair involvement reported after COVID‐19 vaccination have been published in the literature. 35 , 36 , 37 Nonetheless, since our study focused on cutaneous reactions, hair involvement after COVID‐19 vaccination was not examined separately. However, the current study also had several strengths, such as more than 95% of non‐local cutaneous reactions being diagnosed by a dermatologist and the participants being questioned through one‐to‐one interviews.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the recall of the previous episode of AA was not volunteered until the second visit. Most of available literature reported previous history of AA either remote or recent, however, May Lee et al, 2021, and Gallo et al, 2021, have reported cases for the first time [ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gallo et al’s report describes a further case—symptoms, which started 3 weeks after the vaccination, were limited to the scalp and beard. 11 This patient had no personal history of AA or other autoimmune disorders, nor any family history of AA.…”
Section: Postvaccinationmentioning
confidence: 98%